Taxonomy of the Neolycaena (Rhymnaria) davidi (Oberthür, 1881) species group, with the description of two new taxa from Russia and China (Lepidoptera, Lycaenidae) - Krupitsky, Anatoly V. (Zootaxa, 2021)
Poorly known taxa of the Neolycaena (Rhymnaria) davidi (Oberthür, 1881) species group are reviewed in the light of modern findings. The taxon kozlovi Zhdanko, 1996 previously considered a subspecies of N. (R.) davidi is recognised here as a separate species, N. (R.) kozlovi Zhdanko, 1996, stat. rev., including the subspecies N. (R.) kozlovi namkhaidorji Churkin, 2004, comb. nov., based on morphological differences, the geographic isolation and ecological specialisation. A new species, N. (R.) markhasiovi sp. n., is described from Xinjiang Uyghur Autonomous Region in China (Eastern Tian Shan, the Karlik Mountains) on the basis of distinct genitalia morphology and features of the external morphology, including colouration of the female abdomen. Populations of the subgenus Rhymnaria from southern Tuva in Russia (the Tannu-Ola Mountains) are described as a separate subspecies, N. (R.) davidi tannuola ssp. n. A checklist of the taxa of the N. (R.) davidi species group including data on their distribution and host plants is presented, as well as a key to the species of the group.